Clinical Presentation, Renal Histopathological Findings, and Outcome in Patients with Monoclonal Gammopathy and Kidney Disease. (13th May 2021) - Alfano, Gaetano; Delrio, Alice; Fontana, Francesco; Mori, Giacomo; Cazzato, Silvia; Ferrari, Annachiara; Perrone, Rossella; Giovanella, Silvia; Ligabue, Giulia; Magistroni, Riccardo; Cappelli, Gianni
Abstract : Monoclonal gammopathies are associated with acute and chronic kidney injury. Nephrotoxicity of the secreted monoclonal (M)-protein is related to its biological properties and blood concentration. Little is known about epidemiology, clinical manifestations, and outcome of monoclonal gammopathies in patients with kidney disease. We retrospectively collected data about demographics, clinical manifestations, and renal histological lesions of all patients ( n = 1334) who underwent kidney biopsy between January 2000 and March 2017. Monoclonal gammopathy was detected in 174 (13%) patients with a mean age of 66.4 ± 13.1 years. The spectrum of monoclonal gammopathies comprised monoclonal gammopathy of undetermined significate (MGUS) (52.8%), multiple myeloma (MM) (25.2%), primary amyloidosis (AL) (9.1%), smoldering MM (SMM) (4%), non-Hodgkin lymphoma (NHL) (6.8%), and Hodgkin lymphoma (HL) (1.7%). Monoclonal gammopathy of renal significance (MGRS) accounted for 6.5% in patients with MGUS and 14.2% in patients with SMM. Evaluation of kidney biopsy revealed that M-protein was directly involved in causing kidney injury in MM (93.1%). MM was the only gammopathy significantly associated with an increased risk of kidney injury (odds ratio [OR] = 47.5, CI 95%, 13.7–164.9; P ≤ 0.001 ). While there were no significant differences in the progression toward end-stage renal disease or dialysis P = 0.776, monoclonal gammopathies were associated with a different risk of death P = 0.047 at the end of the follow-up. In conclusion, monoclonal gammopathy was a frequent finding (13%) in patients who underwent kidney biopsy. M-protein was secreted by both premalignant (56.8%) and malignant (43.2%) lymphoproliferative clones. Kidney biopsy had a key role in identifying MGRS in patients with MGUS (6.5%) and SMM (14.2%). Among monoclonal gammopathies, only MM was significantly associated with biopsy-proven kidney injury. The rate of end-stage renal disease or dialysis was similar among monoclonal gammopathies, whereas NHL, MM, and SMM showed a higher rate of deaths.